Odziv gozdnega drevja na globalno segrevanje - Levanič, Tom (Gozdarski vestnik, 2017)
Global warming affects forest ecosystems, which can be observed in increased mortality of trees and drying of increasingly larger forest areas. The cause of global warming is an increase of greenhouse gas concentration in the atmosphere, which is a consequence of excessive fossil fuels, deforestation, burning of biomass, intensive agriculture, and traffic. We studied tree response to global warming with the use of dendrochronological methods on sites at the upper forest boundary and in the lowlands of SW Balkan and we have found out, that the first signs of global warming impact on tree growth are already noticeable. At the upper forest boundary, where the temperature has a key impact on the growth, the response is positive at first, in the lowlands, where the key role is played by precipitation, the reduction of precipitation negatively affects the growth and represents the cause for a quick increase in mortality in lowland forests.
Keywords: globalne spremembe; odzivi dreves; global change; dendroklimatologija; tree response; rekonstrukcija klime; climate reconstruction; dendroclimatology; Balkan; Balkans